Inheritance Rights of Children Born Out of Wedlock: Comparative Indonesia and Malaysia Child Protection Radbruch Analysis - Ikwal Pangsa Chaniago; Abd Rouf (AHKAM, 2026)
Constitutional Court Decision No. 46/PUU-VIII/2010 marked a paradigm shift in Indonesian family law by recognizing the legal relationship between children born out of wedlock and their biological fathers, particularly in relation to inheritance rights previously constrained by the absence of marriage registration. This study aimed to analyze the legal implications of the decision through Law No. 35 of 2014 on Child Protection and Gustav Radbruch’s legal values of justice, utility, and legal certainty. The study employed doctrinal and philosophical approaches to evaluate whether the decision fulfills substantive justice and the principle of the best interests of the child. The findings indicate that the decision aligns with Radbruch’s three legal values by advancing child protection and reducing discriminatory treatment against children born out of wedlock. However, a significant gap remains between normative recognition and practical enforcement due to the absence of clear technical regulations and unequal access to DNA testing mechanisms. In comparison, Malaysia applies a more conservative Islamic legal framework, in which children born out of wedlock are legally recognized only in relation to the mother and are excluded from inheritance rights from the biological father under faraid principles, although limited protection may be provided through hibah, wasiat, or state welfare institutions. The study concludes that Constitutional Court Decision No. 46/PUU-VIII/2010 provides an important foundation for strengthening substantive justice and child protection in Indonesia, but its effectiveness depends on clearer regulatory implementation. These findings contribute to the discourse on comparative family law, child protection, and legal philosophy, while offering practical implications for policymakers to strengthen legal certainty and ensure equal protection for all children without discrimination.